Perancangan Desain Kemasan Peyek Kacang UMKM Dapur Kriyuk Menggunakan Metode Kansei Engineering - Setiawati, Ni Luh Putu Lilis Sinta; Dewi, Desak Ayu Sista; Ariasih, Ni Wayan Devi; Pangestu, M. Aditya; Lestari, Ni Wayan Amanda Febry (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
The simplicity of packaging used by small and medium-sized enterprises (SMEs) can affect the low sales of a product. One such product experiencing this issue is the peanut chips product from the SME Dapur Kriyuk. Therefore, redesigning the packaging can be an alternative solution to increase sales. This study aims to determine a packaging design concept that aligns with consumer preferences. The method used is Kansei engineering through a survey involving 114 respondents, which resulted in 50 Kansei words. The survey results showed that 81.58% of respondents indicated the need for improvements to the current packaging. The grouping of 50 Kansei words produced 14 Kansei word attributes, which were then analyzed for their importance to understand the priority or order of importance of the packaging attributes. Based on factor analysis, five factors were identified representing the 14 Kansei word attributes: product aesthetics, packaging functionality, product information, sustainability and hygiene, and price information. These factors then served as a reference in designing two alternative packaging designs, which were further evaluated based on consumer preferences through a survey of 82 respondents. The results of the study showed that the weight score of Design A had a higher Kansei word attribute match score compared to Design B. Design A had a score of 4.39, while Design B had a score of 4.14, making Design A the selected alternative design.